PhyteByte: identification of foods containing compounds with specific pharmacological properties. - Westerman, Kenneth E.; Harrington, Sean.; Ordovas, Jose M.; Parnell, Laurence D. (Tufts University. Tisch Library., 2020)
Keywords: Bioactivity, Food, Molecule, Natural compound, Nutrition, Protein target.; Springer Open.